2018
DOI: 10.1051/0004-6361/201833539
|View full text |Cite
|
Sign up to set email alerts
|

Toward a new paradigm for Type II migration

Abstract: Context.Giant planets open gaps in their protoplanetary and subsequently suffer so-called type II migration. Schematically, planets are thought to be tightly locked within their surrounding disks, and forced to follow the viscous advection of gas onto the central star. This fundamental principle however has recently been questioned, as migrating planets were shown to decouple from the gas' radial drift. Aims. In this framework, we question whether the traditionally used linear scaling of migration rate of a gi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 28 publications
5
57
0
Order By: Relevance
“…The closest work to the one we present here is Robert et al (2018). These authors showed that the migration rate scales with the viscosity, as expected in type II migration.…”
Section: Comparison With Previous Work: Type II Migration Is Correct supporting
confidence: 77%
See 1 more Smart Citation
“…The closest work to the one we present here is Robert et al (2018). These authors showed that the migration rate scales with the viscosity, as expected in type II migration.…”
Section: Comparison With Previous Work: Type II Migration Is Correct supporting
confidence: 77%
“…Lastly, it should be noted that, although mass transport through the gap does happen, it is not the reason for the apparent discrepancy from type II migration. Robert et al (2018) showed that one obtains similar migration rates also when cutting the mass transport through the gap. Along the same lines, our simulations show that the mass transport through the gap decreases with time and eventually becomes smaller than the viscous rate.…”
Section: Comparison With Previous Work: Type II Migration Is Correct mentioning
confidence: 91%
“…This function is based on Robert et al (2018), where the authors assume that close to the planet gas accretion is 100% efficient ( f red = 1). However, it seems that 100% efficiency is not realistic in such a case.…”
Section: The Fargo-2d1d Codementioning
confidence: 99%
“…The main motivation for these studies has, in fact, been the migration of the giant planets that have the capacity to open these deep gaps. However, it is only recently that these migration studies have started to factor in planetary gas accretion (Dürmann & Kley 2015;Crida & Bitsch 2017;Robert et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This would result in a decoupled planetary migration that can differ from the viscous accretion speed (Duffell et al 2014;Dürmann & Kley 2015). Simulations can even have a planet migrating through a stationary disk (Robert et al 2018).…”
Section: Classic Type II Migrationmentioning
confidence: 99%